Strategic Management of Madrasas in Improving Accreditation of Guppi Nurul Jadid Mts in Sumber Sari Village, Tungkal Jaya Sub-District, Musi Banyuasin District - Saputri, Rafhita Ika; Warlizasusi, Jumira; Bahri, Syaiful (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study is based on the accreditation of madrasahs which are still C in the last two accreditation assessments. Strategic management is an approach that can provide an effective framework for achieving educational goals and improving madrasah accreditation. The researcher raised the planning, implementation, evaluation, and strategic management can improve accreditation at MTs Guppi Nurul Jadid. This study uses a descriptive qualitative approach through case studies. Data sources consist of primary and secondary. Data collection techniques with observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions and data validity. The results of the study indicate that the strategic planning process for improving accreditation at MTs Guppi Nurul Jadid includes developing a vision and mission, identifying external opportunities and threats of an organization, and designing strategies to achieve goals to improve accreditation. The implementation of strategic management in improving the accreditation of MTs Guppi Nurul Jadid includes activities to determine madrasah policies, provide motivation by the head of the madrasah, allocate existing resources, and develop a culture that will support the implementation of the strategy. The strategic management evaluation process in improving accreditation includes monitoring activities for educators, education staff, and students and supervising institutional programs. Strategic management can improve madrasah accreditation at MTs Guppi Nurul Jadid through cooperation with all stakeholders and the community, periodic monitoring and evaluation, and human resource development. Keywords: Management, Strategic, Accreditation Improvement, Madrasah